PERAN GUGUS PENJAMINAN MUTU PENDIDIKAN GURU MADRASAH IBTIDAIYAH REGIONAL KALIMANTAN DAN PROGRAM STUDI TERAKREDITASI UNGGUL DALAM PROSES PENJAMINAN MUTU - Rahmad; Syahmidi; Syarifah Salmah (UHN IGB Sugriwa Denpasar, 2024)
SPMI is a systemic activity to guarantee the quality of higher education by each university autonomously or independently to control and improve the implementation of higher education in a planned and sustainable. AMI is a systematic and independent audit activity carried out internally by educational institutions carried out by LPM together with auditors, on units and study. This article aims to describe the implementation of SPMI in universities in Central and South Kalimantan. The subjects selected are members of the selected LPM Campus and then proceed to the management of the PGMI study program. The results of this research are that universities that have a superior title, such as Lambung Mangkurat University, already use an international standard quality assurance system. This is through LPM ULM which has been certified ISO 9001:2015 by SAI Global. UIN Antasari has started implementing the same thing. This is due to the certification of ISO 21001:2018 and ISO 9001:2015 by PT Decra. IAIN Palangka Raya still has not implemented this. Another finding is that the Internal Quality Assurance Activities of the PGMI Study in South Kalimantan and Central Kalimantan have carried out monitoring and evaluation by GPM and carried out by AMI regularly and periodically. Then the Internal Quality Assurance System (SPMI) at IAIN Palangka Raya is on a good track but needs further improvement. For example, this increase was added to SPME in the form of implementing ISO at IAIN Palangka Raya.